2020
DOI: 10.36290/vnl.2020.144
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in the treatment of obesity in practice

Abstract: 3. interní klinika -klinika endokrinologie a metabolismu 1. LF UK a VFN Praha 2 FTVS Praha -Katedra zdravotní TV a tělovýchovného lékařství, Praha 3 3. klinika rehabilitačního lékařství 1. LF UK a VFN Praha 4 ORP centrum, Praha Fyzická aktivita je nedílnou součástí léčby obezity. Až překvapivě i mezi zdravotníky přetrvává hodnocení léčby obezity pouze na základě hmotnostního poklesu. Léčba obezity není však jen prosté snižování hmotnosti, ale především léčba přidružených onemocnění, jako hypertenze, diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previously, beneficial effects of regular exercise were reported in diabetic patients with or without complications and/or only insulin resistance [ 62 , 63 ]. It was reported that HIIT exercises for 8 weeks were shown to improve glycemic control and pancreatic β Cell function, preserve insulin secretion, and enhance insulin sensitivity of type 2 diabetes [ 64 , 65 ]. Additionally, interval training exercise was shown to improve free-living and postprandial glycemic control parameters of diabetic patients when compared to continuous exercise with matched time duration and oxygen consumption [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, beneficial effects of regular exercise were reported in diabetic patients with or without complications and/or only insulin resistance [ 62 , 63 ]. It was reported that HIIT exercises for 8 weeks were shown to improve glycemic control and pancreatic β Cell function, preserve insulin secretion, and enhance insulin sensitivity of type 2 diabetes [ 64 , 65 ]. Additionally, interval training exercise was shown to improve free-living and postprandial glycemic control parameters of diabetic patients when compared to continuous exercise with matched time duration and oxygen consumption [ 66 ].…”
Section: Discussionmentioning
confidence: 99%